2000
DOI: 10.1046/j.1469-7580.2000.19730437.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of human intracardiac nerves: an electron microscope study

Abstract: Since many human heart diseases involve both the intrinsic cardiac neurons and nerves, their detailed normal ultrastructure was examined in material from autopsy cases without cardiac complications obtained no more than 8 h after death. Many intracardiac nerves were covered by epineurium, the thickness of which was related to nerve diameter. The perineurial sheath varied from nerve to nerve and, depending on nerve diameter, contained up to 12 layers of perineurial cells. The sheaths of the intracardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 58 publications
1
36
0
1
Order By: Relevance
“…The dense cholinergic innervation of SAN region has been previously demonstrated in a range of mammalian species that have applied histochemical staining for AChE [3][4][5][6][7][8] as well as by immunohistochemistry for choline transporters [9] and choline acetyltransferase [10]. The data presented with the current study confirm earlier electron microscope observations about distribution of unmyelinated nerve fibres within sinoatrial node area in the mouse [13], rabbit [15] and human [33]. Despite this, we did not confirm previous electron microscope observations concerning the distribution of myelinated nerve fibres that were characteristic for rabbit SAN [15].…”
Section: Ultrastructuresupporting
confidence: 93%
“…The dense cholinergic innervation of SAN region has been previously demonstrated in a range of mammalian species that have applied histochemical staining for AChE [3][4][5][6][7][8] as well as by immunohistochemistry for choline transporters [9] and choline acetyltransferase [10]. The data presented with the current study confirm earlier electron microscope observations about distribution of unmyelinated nerve fibres within sinoatrial node area in the mouse [13], rabbit [15] and human [33]. Despite this, we did not confirm previous electron microscope observations concerning the distribution of myelinated nerve fibres that were characteristic for rabbit SAN [15].…”
Section: Ultrastructuresupporting
confidence: 93%
“…10 In dogs, it is the offspring of the ventrolateral nerve. 7 Besides these 3 major nerves, small cardiac nerves arise from various cardiopulmonary plexus and the thoracic vagal nerves that innervate overlapping regions of the LV 11,19,20 or right ventricle. 21 On the basis of functional and anatomic analyses, most likely sympathetic efferent fibers of the left lateral cardiac nerve were stimulated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Previous anatomic studies have shown that sympathetic fibers also cross the coronary sinus (CS). 10,11 To identify these fibers, a deflectable 8-mm-tip multielectrode catheter (Cordis Corp) was introduced inside the CS via the left jugular vein and connected to an external stimulator (Grass-S-88 stimulator, Astro-Med Inc, West Warwick, RI). To avoid inadvertent electric stimulation of the atria or ventricles, high-frequency stimulation (HFS) trains within the myocardial refractory periods (train duration, 50 ms; frequency, 200 Hz; 37.5 V; 2-ms pulse duration) were coupled to the pacing stimulus during atrial (nϭ20) or ventricular (nϭ8) pacing at a delay of 20 ms.…”
Section: Sympathetic Nerve Stimulationmentioning
confidence: 99%
“…Intrinsic cardiac neurons, first identified on the human heart by Scarpa in 1794 (cited by Mitchell et al, 1952), have been described in a variety of mammalian species (Dogiel, 1899; Francillon, 1928; Kuntz, 1934; Davies et al, 1952; King and Coakley, 1958; Robb, 1965; Shvalev and Sosunov, 1985; Gagliardi et al, 1988; Yuan et al, 1994; Armour et al, 1997; Pauza et al, 1997, 2000). Intrinsic cardiac neurons are concentrated in collections of ganglia and interconnecting nerves that form identifiable ganglionated plexuses within epicardial fat (Gagliardi et al, 1988; Yuan et al, 1994; Armour et al, 1997; Pauza et al, 2000; Pauziene et al, 2000). Although the neurons are typically found in epicardial fat at the base of the atria, in the interatrial septum and on the cranial aspects of the ventricles, there is considerable interspecies variation in the gross topographical (anatomical) distributions of the somata of intrinsic cardiac neurons on the mammalian heart.…”
mentioning
confidence: 99%